PENGEMBANGAN MEDIA PEMBELAJARAN KOMIK ASAL MULA SUNGAI LEMBU PETENG UNTUK MENINGKATKAN KEMAMPUAN MENGURAIKAN PESAN DALAM DONGENG KELAS III SD ISLAM AL IKLHAS KARANGREJO - Sari, Vrenti Prima Mustika; Laila, Alfi; Mujiwati, Endang Sri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Learning Indonesian has a very important role, not only for communication skills but also for scientific purposes. In learning Indonesian in elementary schools there are four aspects of skills that students need to master, namely listening, speaking, reading and writing. This research aims to determine the validity, practicality and effectiveness of the Comic Learning Media Origins of the Lembu Peteng River to improve the ability to decipher messages in fairy tales for Class III at Al-Iklhas Islamic Elementary School, Karangrejo. One of the comic learning media development models used in this research is the ADDIE model. The ADDIE development model consists of five stages (1). Analysis (2). Design (3). Development (4). Implementation (5) Evaluations. The subjects of this research were 30 students in class III of Al Iklhas Islamic Elementary School, Karangrejo. The analysis technique used is quantitative and qualitative data analysis. The results of this research are as follows: (1) Comic media with moral message material in fairy tales is declared very valid because the criteria for obtaining media validation results is 86%, (2) Comic media with moral message material in fairy tales is declared very effective in learning because of the completeness of student learning in post -limited trial test which obtained an average score of 88, and a post-test extensive trial score of 98.50, (3) Comic media, moral message material in fairy tales was declared practical because the results of teacher responses obtained a percentage of 98%, the results of student responses the limited test was 99%, and the student response to the broad test was 98%. Keywords: Comic Media, Moral Message Material in Fairy TalesLearning Indonesian has a very important role, not only for communication skills but also for scientific purposes. In learning Indonesian in elementary schools there are four aspects of skills that students need to master, namely listening, speaking, reading and writing. This research aims to determine the validity, practicality and effectiveness of the Comic Learning Media Origins of the Lembu Peteng River to improve the ability to decipher messages in fairy tales for Class III at Al-Iklhas Islamic Elementary School, Karangrejo. One of the comic learning media development models used in this research is the ADDIE model. The ADDIE development model consists of five stages (1). Analysis (2). Design (3). Development (4). Implementation (5) Evaluations. The subjects of this research were 30 students in class III of Al Iklhas Islamic Elementary School, Karangrejo. The analysis technique used is quantitative and qualitative data analysis. The results of this research are as follows: (1) Comic media with moral message material in fairy tales is declared very valid because the criteria for obtaining media validation results is 86%, (2) Comic media with moral message material in fairy tales is declared very effective in learning because of the completeness of student learning in post -limited trial test which obtained an average score of 88, and a post-test extensive trial score of 98.50, (3) Comic media, moral message material in fairy tales was declared practical because the results of teacher responses obtained a percentage of 98%, the results of student responses the limited test was 99%, and the student response to the broad test was 98%.